PENGARUH PENAMBAHAN TEPUNG KULIT BUAH NAGA (Hylocereus polyrhizus) TERHADAP PENINGKATAN KECERAHAN WARNA PADA IKAN GUPPY PLATINUM RED TAIL(Poecilia reticulate) DI BALAI BENIH IKAN KABUPATEN SIDOARJO - Qotrunada Drajat Widya Utami (Universitas Mataram, 2026)
The Platinum Red Tail Guppy (Poecilia reticulata) is a freshwater ornamental fish with high economic value, largely determined by its color quality. This study aimed to determine the effect and optimal dosage of red dragon fruit (Hylocereus polyrhizus) peel flour as a natural pigment source in enhancing color brightness. The study was conducted for 30 days using four dosage treatments (0%, 10%, 15%, dan 20%). The results showed that the addition of red dragon fruit peel flour significantly improved color brightness, with the 15% dosage producing the best result. Red dragon fruit peel flour has potential as an environmentally friendly natural pigment source in guppy aquaculture.